Direct measurement of the top quark mass by the DO Collaboration - Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alves, G; Amos, N; Anderson, E; Astur, R; et al. (1998)
We determine the top quark mass mt using tt pairs produced in the DØ detector by √s=1.8TeV pp collisions in a 125 pb-1 exposure at the Fermilab Tevatron. We make a two constraint fit to m1 in tt→bW+bW- final states with one W boson decaying to qq and the other to ev or μv. Likelihood fits to the data yield mt(l+jets)= 173.3±5.6 (stat) ±5.5 (syst) GeV/c2. When this result is combined with an analysis of events in which both W bosons decay into leptons, we obtain mt= 172.1 ±5.2 (stat) ±4.9 (syst) GeV/c2. An alternate analysis, using three constraint fits to fixed top quark masses, gives mt(l+ jets) = 176.0 ±7.9 (stat)± 4.8 (syst) GeV/c2, consistent with the above result. Studies of kinematic distributions of the top quark candidates are also presented. © 1998 The American Physical Society.